Effect of obesity on Covid-19 anxiety and role of self-esteem on women: Obestiy and Covid-19 anxiety - Altunal, Çetin; Borku Uysal, Betül; İslamoğlu, Mehmet Sami (Progress in Nutrition, 2023)
In this prospective study, it was aimed to evaluate effects of obesity on Covid-19 anxiety and role of self-esteem on women. Obese (n = 184) and non-obese women (n = 219) who applied to our clinic in the first six months of 2020 were included in the study. The women included in the study were divided into two groups as having Body Mass Index (BMI) 30 or more obese according to the WHO criteria. Demographic information form, the Rosenberg Self-Esteem Scale and the Covid-19 Anxiety Scale was used for data collection. Most of the obese participants were housewives, and the difference was statistically significant (p<0.05). Family obesity history was more common at obese group with statistically significant difference (p<0.05). Rosenberg self-esteem were lower and Covid-19 Anxiety levels were higher in obese patients with statistically significant differences (p<0.05). obesity, working status and family history were significantly correlated with Covid-19 anxiety (p<0.01). According to GLM model, only obesity had positive contribution to Covid-19 anxiety at multivariate level (p<0.05). The level of Covid-19 anxiety is higher in obese women, and the increase in self-esteem levels decreases this anxiety level. In order to reduce this burden, the news and content that indicate obesity as a risk factor in publications about the pandemic should be planned considering the self-esteem of these individuals.